2022
DOI: 10.1016/j.ijregi.2022.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome coronavirus 2 antibody seroprevalence in Lebanon: a population-based cross-sectional study

Abstract: Objectives The World Health Organisation promoted the use of serological testing as a rapid and accurate technique for detection of the immunity against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). In Lebanon, a better understanding of the immune response against SARS-CoV-2 is needed to develop effective measures for prevention and plan an appropriate national vaccination program. This study aims to measure the immunity status in Lebanon. Methods In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…[89] SARS-CoV-2 seroprevalence studies are important to estimate the burden of COVID-19 in a population and to understand the disease transmission dynamics, risk of infection as well as the future and the evolution of the pandemic [90]. While serosurveys are important to guide the public health response, unfortunately, few seroprevalence studies on anti-SARS-CoV-2 antibodies were performed in Lebanon with most of them using sera collected early during the pandemic [91][92][93]. The results of these studies showed a gradual increase in seropositivity from 2.7% (November 2020) to 84.8% (April 2021) [91,93].…”
Section: Epidemiologic and Genomic Surveillance Of Sars-cov-2mentioning
confidence: 99%
See 3 more Smart Citations
“…[89] SARS-CoV-2 seroprevalence studies are important to estimate the burden of COVID-19 in a population and to understand the disease transmission dynamics, risk of infection as well as the future and the evolution of the pandemic [90]. While serosurveys are important to guide the public health response, unfortunately, few seroprevalence studies on anti-SARS-CoV-2 antibodies were performed in Lebanon with most of them using sera collected early during the pandemic [91][92][93]. The results of these studies showed a gradual increase in seropositivity from 2.7% (November 2020) to 84.8% (April 2021) [91,93].…”
Section: Epidemiologic and Genomic Surveillance Of Sars-cov-2mentioning
confidence: 99%
“…While serosurveys are important to guide the public health response, unfortunately, few seroprevalence studies on anti-SARS-CoV-2 antibodies were performed in Lebanon with most of them using sera collected early during the pandemic [91][92][93]. The results of these studies showed a gradual increase in seropositivity from 2.7% (November 2020) to 84.8% (April 2021) [91,93]. This increase was expected due to the unprecedented rise in the number of COVID-19 cases detected during the same period (Figure 1A).…”
Section: Epidemiologic and Genomic Surveillance Of Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“…The SARS-CoV-2 virus has caused a global pandemic, infecting millions of individuals worldwide. Coronavirus disease caused by SARS-CoV-2 typically presents with respiratory symptoms such as fever, cough, and shortness of breath [1,2]. However, numerous studies have reported a variety of extra-pulmonary symptoms and complications of COVID-19, including gastrointestinal (GI), cardiovascular, and neurological symptoms.…”
Section: Introductionmentioning
confidence: 99%